Historical Researches about Anton Semenovitch Makarenko - Mettini, Emiliano (Pedagogical Discourse, 2013)
Our article sets itself as a goal to provide an analysis of the historical researches about Anton Semenovitch Makarenko in Western Germany and Italy after the end of the World War Two until today. Researchers and scientists of these countries chose Anton Semenovitch Makarenko because in him, in spite of the difference of their own political views with those of the great pedagogue and educator, the source of a really democratic system education for the new generations.